2020
DOI: 10.1182/blood-2020-139803
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Gene Therapy Study of AAVhu37 Capsid Vector Technology in Severe Hemophilia A - BAY 2599023 has Broad Patient Eligibility and Stable and Sustained Long-Term Expression of FVIII

Abstract: Background Gene therapy for hemophilia A has the potential to reduce the treatment burden for patients and their care providers by eliminating the need for regular factor VIII (FVIII) prophylaxis through long-term expression of endogenous FVIII at levels sufficient to provide bleed protection. Host immunity to the capsid serotype limits patients' eligibility and may impact the balance between vector dose and clinical outcome. BAY 2599023 (AAVhu37FVIII) is the first clinical-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In 2010, Wang et al showed a seroprevalence rate for AAV-hu37 neutralizing antibodies of approximately 15% (based on a titer of greater than 1:20) in 40–100 human serum samples [ 114 ]. More recently, the seroprevalence of AAV-hu37 was assessed by determining neutralizing antibody levels according to cellular transduction inhibition in 100 US patients with hemophilia A. Neutralizing antibodies against AAV5 and AAV8 were also measured [ 115 ]. The study showed that AAV-hu37 had a low pre-existing neutralizing antibody prevalence.…”
Section: Characteristics Of the Bay 2599023 (Aavhu37hfviiico) Gene Th...mentioning
confidence: 99%
“…In 2010, Wang et al showed a seroprevalence rate for AAV-hu37 neutralizing antibodies of approximately 15% (based on a titer of greater than 1:20) in 40–100 human serum samples [ 114 ]. More recently, the seroprevalence of AAV-hu37 was assessed by determining neutralizing antibody levels according to cellular transduction inhibition in 100 US patients with hemophilia A. Neutralizing antibodies against AAV5 and AAV8 were also measured [ 115 ]. The study showed that AAV-hu37 had a low pre-existing neutralizing antibody prevalence.…”
Section: Characteristics Of the Bay 2599023 (Aavhu37hfviiico) Gene Th...mentioning
confidence: 99%
“…The same team that ushered haemophilia B gene therapy back into the clinic designed several AAV vectors encoding B domain‐deleted (BDD) FVIII, one of which was selected for clinical development and became BMN 270 in 2014, now in Phase 3 57–60 . It was the first clinical trial that achieved normal FVIII levels in some individuals, and several other studies soon followed having similar success with different vectors 61–64 . Four clinical programs have advanced to Phase 3 with some early phase studies having multiyear data 57,62,65,66 …”
Section: New Hopes and Old (And New) Worriesmentioning
confidence: 99%
“…[57][58][59][60] It was the first clinical trial that achieved normal FVIII levels in some individuals, and several other studies soon followed having similar success with different vectors. [61][62][63][64] Four clinical programs have advanced to Phase 3 with some early phase studies having multiyear data. 57,62,65,66 After decades of disappointments, the first gene therapies for haemophilia A and B are nearing commercialization, and thus the longawaited cure has come within reach but not for everyone.…”
Section: New Hopes and Old (And New) Worriesmentioning
confidence: 99%
“…Nevertheless, sustained expression of FVIII from hepatocytes has been associated with greater interindividual variability in these trials than was experienced in hemophilia B gene therapy. Liver transaminitis and apparent cellular immunity initiating or re-initiating at late time points (more than three to four months following gene transfer) had not been observed in hemophilia B trials but has been reported in several hemophilia A trials [8,[35][36][37][38][39][40]. Supportive courses of corticosteroids, whether used in a reactive or prophylactic fashion, have in several trials greatly exceeded the duration used in hemophilia B trials [8,19,35,36,[38][39][40], resulting in steroid-associated adverse events and calling into question whether adjunctive or alternative immune modulating agents should be used.…”
Section: Figurementioning
confidence: 99%
“…Liver transaminitis and apparent cellular immunity initiating or re-initiating at late time points (more than three to four months following gene transfer) had not been observed in hemophilia B trials but has been reported in several hemophilia A trials [8,[35][36][37][38][39][40]. Supportive courses of corticosteroids, whether used in a reactive or prophylactic fashion, have in several trials greatly exceeded the duration used in hemophilia B trials [8,19,35,36,[38][39][40], resulting in steroid-associated adverse events and calling into question whether adjunctive or alternative immune modulating agents should be used. A challenge for the field of hemophilia A gene therapy, which provides context for this review, will be to understand to what extent these apparent inflammatory phenomena, as well as the decline in FVIII expression reported in one trial [8], result from immune mechanisms or from mechanisms that are not purely immune in origin (e.g., constraints of synthesis of factor VIII in hepatocytes rather than liver sinusoidal endothelial cells; natural senescence and turnover of hepatocytes) and what mitigating strategies will best balance benefit and risk.…”
Section: Figurementioning
confidence: 99%